Perception and Challenges of Select Higher Educational Institutions on its Role in the Technology Business Incubation in the Visayas, Philippines - Ybañez, Adrian P.; Mendoza, Siegfried D.; Caintic, Cristina; Sabayton, Mae S. (UI Scholars Hub, 2021)
Research Aims: The present study aims to document perceptions and identify the challenges on the participation and role of technology business incubators (TBIs) of select academic institutions in Visayas, Philippines. Design/methodology/approach: It is quantitative-qualitative research, which utilized survey questionnaires and focus group discussion of twenty-five (25) key informants (KIs) from nine higher education institutions (HEIs) in the Visayas. KIs include key officials and faculty who handled research, technology transfer, business incubation, intellectual property, and/or technology licensing functions in their respective HEIs. Research Findings: All KIs were from state universities or colleges, and most KIs were female (64%), married (60%), and holders of a doctorate degree (72%). Results showed that most KIs had good knowledge of TBI operations and intellectual property rights, but acknowledged the need for developing capacities and facilities for the TBI operations. Theoretical Contribution/Originality: This study identified key challenges and concerns of the HEIs that can affect the implementation and operations of the TBI program in the Philippines which include the training needs of the faculty, lack of manpower and budget, and the sustainability of the facility/operation. The HEIs also need support from government agencies and non-government organizations. Managerial Implication in the South East Asian context: TBI can help in the improvement of the country's innovation index, technopreneurship, and value creation. Philippine HEIs should consider the cost and sustainability of setting up TBIs as well as how they benchmark their activities against other Southeast Asian countries. Research limitation & implications: Although the sample appears to be limited, data was collected from key HEI managers and decision-makers. Therefore, this study can still provide insights for current and prospective TBIs to help address common concerns and formulate policies and strategies for the operations and sustainability of the program in their respective HEIs.